OUTCOME OF COMBINATION THERAPY VERSUS BEHAVIOR THERAPY IN TREATMENT OF NOCTURNAL ENURESIS - Haﬁza Nuzhat; Imran Qadir; Muhammad Tahir Bashir Malik (Journal of University Medical & Dental College, 2017)
ABSTRACT: Nocturnal Enuresis (NE) is the involuntary urination during sleep after the age at which bladder control usually occurs. It is a socially stigmatizing and stressful condition which aﬀects around 15%-20% of ﬁve years old. Various treatment options for PNE include behavioral therapy, alarm therapy, pharmacotherapy and combinations. Current study was aimed to evaluate outcome of behavioral therapy alone and in combination with pharmacological treatment. OBJECTIVE: To compare the outcome of behavioral therapy alone and in combination with pharmacotherapy in management of NE. OPERATIONAL DEFINITION: Behavioral therapy was performed with prompted voiding (voiding by clock) at day time & reducing ﬂuid intake at bedtime. Pharmacotherapy was performed with orally administered imipramine at bedtime. MATERIAL AND METHOD: STUDY DESIGN: Comparative study. SETTING: Urology department, Children Hospital, Faisalabad. SAMPLING: One hundred & thirty consecutive children in age range of 5-13 years with nocturnal enuresis were enrolled in the study and randomly allocated in two groups. One group was advised behavioral treatment alone and other was advised pharmacotherapy (imipramine) along with behavioral therapy.The children with known urinary tract pathologies/congenital anomalies, active urinary tract infection, acquired urologic disease, neurologic diseases and children with daytime LUTS were excluded from the study. Results: At ﬁrst follow up (15-days), in group-A (behavioral therapy alone), 7.7% children reported complete resolution of NE, 23.1% showed improvement (reduction in episodes of NE) and 69.2% showed no improvement. At ﬁrst follow up (15-days), in group-B (combination therapy), 15.4% children reported complete resolution of NE, 61.5% showed improvement (reduction in episodes of NE) and 23.1% showed no improvement. At second follow up (30-days), in group-A (behavioral therapy alone), 38.5% children reported complete resolution of NE, 38.5% showed improvement (reduction in episodes of NE) and 23% showed no improvement. At second follow up (30-days), in group-B (combination therapy), 38.5% children reported complete resolution of NE, 46.2% showed improvement (reduction in episodes of NE) and 15.4% showed no improvement. CONCLUSION: Behavioral therapy can be oﬀered as an initial treatment step in management of nocturnal enuresis. However, combination therapy (behavioral +pharmacotherapy) gives an overall better outcome in the treatment of Nocturnal Enuresis as compared to behavioral therapy alone.